Effect of Integration Life Skills Program (Golf) on Social Competence Among Male Sport Science Students in Indonesia - Ahmad Hamidi (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
This study aimed to investigate the effect of life skill program intervention integrated into golf for eight weeks on the social competence of sports science students. The participants were 22 male students in their late adolescent period divided into two sample groups, namely the experimental group (n = 11 people) and the control group (n = 11 people).). The intervention class was held for 60 minutes, three days a week, for eight weeks. The test measurements were carried out during week one and week 8. The life skill sport scale (LSSS) instrument was given before and after the 2-month intervention. The method used was the quasi-experimental method. The results showed a difference in the pre-test life skill scores between the intervention class (147.5 ± 3.03) and the control class (145.9 ± 2.92), where the intervention group gained ???? = -14.0.45, P= .000. Significant differences occurred in the life skill post-test scores (168.9 ± 1.7 with 151.3 ± 2.5, t = -9.712, P = .004). After two months of intervention, the gain scores were obtained (Gain Score 21.4 versus 5.4 and Percent Gain 14.51% versus 3.70, both obtained P-value=0.000). The finding showed a high level of life skills in the pre-test scores of the two groups. However, a significant improvement was found in the post-test results of the intervention. It indicates that golf can improve male student life skills, especially their social competence.